Production of briquettes from Indonesia agricultural biomass waste by using pyrolysis process and comparing the characteristics - Sri Wahyu Murni; Tutik Muji Setyoningrum; Muhamad Maulana Azimatun Nur (Eksergi, 2021)
Indonesia biomass waste is a potential feedstock as a source of renewable energy since it can be converted into carcoal briquettes. However, the production of the briquettes using pyrolysis process using the agricultural waste was lacking. In this research, briquette was made from palm shells,  corncob and soybean stem wood due to its high availability and have high cellulose content. The purpose of this research was to produce briquettes from three kind of raw materials by employing pyrolysis process and compared the characteristics. The briquette was made from different type of raw materials (palm shells, corncob and soybean stem) and  the concentration of binder : 3-7 %. Pyrolysis was done at  500 °C, and 100 kg / cm2 of pressing pressure. Results showed that, the best charcoal briquette was achieved from palm shells by using 5% binder, which resulted 4,1% moisture content, 3.4% ash content,  15% volatile matter content, 77.5% carbon content,  7075 cal/g calorific value and  1.4 kg/cm2 compresive strength. It is found that the concentration of binder and raw material influenced the quality of the briquettes. In overall, the production of the briquettes by employing pyrolysis method could meet the standard.